What makes summer vacation experience memorable? : an empirical study from Croatia - Lončarić, Dina (Array, 2018)
This paper aims to examine what kind of experience makes summer vacation memorable and consequently how it influences the overall satisfaction with a vacation experience. Based on literature review hypotheses were formulated in order to explore the multidimensionality of memorable tourist experience, the influence of different elements of memorable tourist experience on satisfaction with tourist vacation as well as the influence of satisfaction with vacation experience on the behavioural intention of tourists. For the purpose of the research, empirical research using paper and pencil questionnaire was carried out on the sample of 134 international tourists who visited traditional sun and sea destinations in Croatia in a broader Kvarner region during the summer of 2017. The research results, although of indicative nature only, point out that a memorable tourist experience consists of four different factors, namely hedonism and novelty, local culture, involvement and refreshment. Among them, local culture has the highest impact on overall satisfaction with summer vacation experience. Also, refreshment as a memorable tourist experience influences the overall vacation satisfaction. The research has also confirmed the positive relationship between the following elements: satisfaction with vacation experience on behavioural intentions that were measured through tourists’ intention to return to the destination, to recommend the destination to their friends and relatives, to share experience through social media and to spend more money in tourist destinations. The strongest relationship is between tourist satisfaction with vacation experience and the intention to recommend a destination followed by intention to revisit that destination if they feel satisfied with the experience provided. Managerial implications as well as limitations and ideas for further research are given.